To Find the Effect of Microsurgical Varicocelectomy on Serum Testosterone and FSH Hormones in Infertile Men - Mir Abid Jan, Syed Zia Ur Rahman, Khalil Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: A common and perhaps treatable cause of male infertility, varicocele is frequently linked to altered testicular hormone activity and decreased spermatogenesis. Because to impaired Leydig cell activity, it is known to alter blood testosterone levels adversely and is especially common in men with primary infertility. Although microsurgical varicocelectomy is regarded as the gold standard of care, further research is needed to determine its effects on hormonal profiles, particularly those of testosterone and follicle-stimulating hormone (FSH). Objective: To evaluate the effect of microsurgical varicocelectomy on serum testosterone and FSH levels in infertile men with clinical varicocele. Methodology: The Institute of Kidney Disease (IKD), Medical Teaching Institution (MTI), Hayatabad Medical Complex (HMC), Peshawar, carried out this prospective observational study between 1st May 2023 to 30th Oct 2023. Using non-probability successive sampling, 100 infertile males with clinical Grade II or III varicocele were included in the study. Preoperative baseline levels of FSH and testosterone were measured, and three months after microsurgical subinguinal varicocelectomy, follow-up levels were evaluated. Pairwise t-tests were used to examine hormonal changes, with a significance level of p<0.05. Results: A statistically significant increase in mean serum testosterone was observed postoperatively, with a greater rise noted in hypogonadal men. Serum FSH levels showed a modest but significant decrease following surgery. Patients with Grade III varicocele experienced a more pronounced hormonal response. Conclusion: Microsurgical varicocelectomy significantly improves testosterone levels and moderately reduces FSH levels in infertile men, particularly in those with baseline hypogonadism and higher-grade varicoceles. Keywords: FSH, Hormonal Profile, Infertility, Microsurgical Varicocelectomy, Testosterone, Varicocele